(untitled) (Journal of International Crisis and Risk Communication Research, 2023)
CSR crises occur when organizations fail to live up to publics’ expectation of their social responsibilities. The anger activism model (AAM) uses two variables, efficacy and anger, to explain people’s participation in social movements. Since CSR crises are often value-based and lead to consumer boycotts, AAM sheds light on explaining people’s behaviors in CSR crises. In applying AAM, this study aims to explore effective crisis response strategies and if conditional factors influence the effectiveness of these strategies, using a 2 (strategy: reform vs. refutation) × 2 (proxy efficacy: high vs. low) online experiment in the context of a company’s decision on whether to withdraw its business from Russia in response to the 2022 Russian invasion of Ukraine. The results revealed that reform was a more effective strategy than refutation. In addition, anger moderated the influence of crisis responses on account acceptance, attitude, trust, and boycott intention. As anger increases, refutation becomes less effective.